The Use of Artificial Intelligence to Improve Digital Marketing Strategies for MSMEs in Indonesia - Laksmono, Rendro; Zulfikri, Agung; Priyana, Yana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores the application of Artificial Intelligence (AI) in enhancing digital marketing strategies among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. As digital transformation accelerates globally, MSMEs face growing pressure to adopt innovative technologies to remain competitive. However, challenges such as limited financial resources, low digital literacy, and lack of strategic understanding often hinder effective adoption. Using a qualitative approach, this research conducted in-depth interviews with five MSME owners from various sectors—including food and beverage, fashion, creative design, handicrafts, and online education—who have integrated AI tools into their marketing operations. The findings reveal that AI technologies such as chatbots, predictive analytics, recommendation systems, and automated advertising significantly improve marketing efficiency, customer engagement, and data-driven decision-making. Nonetheless, barriers persist, including high implementation costs, limited technical expertise, and data privacy concerns that restrict broader utilization. The study concludes that successful AI integration among MSMEs depends on three key factors: technological accessibility, organizational readiness, and supportive policy environments. These findings emphasize the strategic role of AI as a catalyst for digital competitiveness and sustainable business growth. Therefore, continuous digital training, affordable AI tools, and strong government–industry collaboration are essential to empower MSMEs in Indonesia’s evolving digital economy.